Lack of Cardiotoxicity Endpoints in Prospective Trials Involving Chest Radiation Therapy: A Review of Registered, Latter-Phase Studies - Prasad, Rahul N.; Miller, Eric D.; Addison, Daniel; Bazan, Jose G. (Frontiers in Oncology, 2022)
Background: Chest radiation therapy (RT) has been associated with increased cardiac morbidity and mortality in numerous studies including the landmark Darby study published in 2013 demonstrating a linear increase in cardiac mortality with increasing mean heart radiation dose. However, the extent to which cardiotoxicity has been incorporated as an endpoint in prospective RT studies remains unknown. Methods: We queried clincaltrials.gov to identify phase II/III trials in lung, esophageal, lymphoma, mesothelioma, thymoma, or breast cancer from 1/1/2006-2/1/2021 enrolling greater than 100 patients wherein chest RT was delivered in at least one treatment arm. The primary endpoint was the rate of inclusion of cardiotoxicity as a specific primary or secondary endpoint in the pre- (enrollment started prior to 1/1/2014) versus post-Darby era using the Chi-square test (p<0.05 considered significant). We also analyzed clinical trial factors associated with the inclusion of cardiotoxicity as an endpoint using logistic regression analysis. Results: In total, 1,822 trials were identified, of which 256 merited inclusion. 32% were for esophageal, 31% lung, 28% breast, and 7% lymphoma/thymoma/mesothelioma cancers, respectively. 5% (N=13) included cardiotoxicity as an endpoint: 6 breast cancer, 3 lung cancer, 3 esophageal cancer, and 1 lymphoma study. There was no difference in the inclusion of cardiotoxicity endpoints in the pre-Darby versus post-Darby era (3.9% vs. 5.9%, P=0.46). The greatest absolute increase in inclusion of cardiotoxicity as an endpoint was seen for lung cancer (0% vs. 6%, p=0.17) and breast cancer (5.7% vs. 10.8%, p=0.43) studies, though these increases remained statistically non-significant. We found no clinical trial factors associated with the inclusion of cardiotoxicity as an endpoint. Conclusions: Among prospective trials involving chest RT, cardiotoxicity remains an uncommon endpoint despite its prevalence as a primary source of toxicity following treatment. In order to better characterize cardiac toxicities, future prospective studies involving chest RT should include cardiotoxicity endpoints.